First Report of Sap Sucking insect pests on Dalbergia latifolia (Roxb.) from Non natural Growing Region of India - Kumar, Arvind; Rajwar, Neha (Indian Forester, 2025)
Insect pests infesting Dalbergia latifolia were documented within plantations located in non-native regions of India. Although D. latifolia has been introduced to various regions in India, there is a lack of comprehensive research on insect pest record. To evaluate the prevalence of insect pests in newly established growth areas of D. latifolia, systematic observations were conducted in Uttarakhand. Many insect pests infesting D. latifolia were recorded so far, though infestation of four insect pests, namely Ricania speculum, Leptocorisa acuta, Leptocentrus taurus, and Dorsicha stebbingi, on Dalbergia latifolia were exhibited for the first time. The research also uncovered the nature of the damage inflicted by these insect pests and their seasonal occurrence patterns. This periodic data on insect pest infestations can prove invaluable for the sustainable management of insect pests and the preservation of D. latifolia in the region.